A Case of Epitheloid Gell Granuloma Disease Node Arising from Ileocaecal Lymph Node - Anzai, T. (Nippon Daicho Komonbyo Gakkai Zasshi, 1973)
A case of epitheloid cell granuloma disease was met with by us which arose from the ileocaecal lymph node. This case found out only by histopathological examination after doubtful preoperative and postoperative diagnosis. The patient was a 31 year old male, a cast-iron worker. About March, 1971, he went to a hospital in his neighborhood, complaining of a pain in the right lower abdomen, emaciation and poor appetite, and his case was diagnosed as chronic gastritis. He underwent treatment for about 5 months as outpatient. In December of the same year, he was hospitalized for two weeks under the diagnosis of acute hepatitis. Again, on February 14 of the next year, he was hospitlized for 2 months under the diagnosis of acute bronchitis. Then in March, the same year this case was diagnosed as right uretero-lithiasis and was transferred to this hospital. Findings Blood examination : erythrocytes 3, 820, 000; leucocytes 8, 200;Sahli's test 72%; Al-p 7, 0; T-p 6-9; ASLO 100, CRP +6; R-A (-). Abdominal findings : On palpation something tumorous was felt around the surgical wound from appendectomy, but we were not able to tell exactly what it was due to the strong tension of the abdominal wall. On histopathological examination, epitheloid cells were seen accompanied by a number of Langerhans's giant cells and foreign giant cells, and so the case was suspected, first of all, to be sarcoidosis. Kveim's reaction was negative. No shadow was seen in the lungs. Since this case developed on a single organ, we will report it as epitheloid cell granuloma disease, following the view adopted by the 6 th International Conference on Sarcoidosis.